Model of Tourist Visiting Decision for Agritourism in Lampung Province - Chairunnisa, Siti Maharani; Hubeis, Musa; Munandar, Jono Mintarto (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Indonesia has major potential in utilizing agricultural-based tourism or what is known as agritourism. The concept of agritourism is quite popular globally and is recognized to support agricultural growth through diversification of activities that generate income for farmers and lead to rural development. Lampung Province is one of the provinces that focuses on developing agritourism areas. Agritourism in Lampung has been new intensively developed in 2018, so it still needs development in advancing the agritourism sector. Research that focuses on tourist decision factors to visit is important to carry out.Purpose: The purpose of this study is to identify the characteristics and visiting decision models of agritourism tourists in Lampung. Design/methodology/approach: This research used Structural Equation Modelling (SEM) analysis. Findings/Result: The study's findings indicate that the extended TPB model has a favourable impact on traveller’s decisions to travel. The intention of tourists to visit is unaffected by anything but subjective norms. Optimizing the attractions and products is crucial in forming a positive attitude among tourists in agritourism visit decision. Providing facilities and infrastructure can also be done to increase the number of visits to agritourism. Conclusion: Attitude as the most contributing variable in shaping the behavior of tourist visits to agritourism, makes agritourism actors need to provide attractive facilities including unique decorations, adding photo spots, adding children's educational spots, providing more family leisure spaces, and providing facilities that support child-friendly activities. The addition of innovation in agricultural education activities also needs to be added to provide a perception of authenticity for agritourism related to superior or characteristics commodities in Lampung Province. This will make the image of agritourism in Lampung Province as a destination that provides pleasure and education for tourists.Originality/value (State of the art): This study uses the TPB concept in analyzing tourist behavior in visiting agritourism of Lampung Province. Previous research using the TPB concept has been conducted in the context of tourists in agritourism by adding variables of perception of authenticity and environmental concern. This study expands the concept of TPB by improving and adding other variables that have an influence in shaping tourist behavior such as destination image, family influence, eWOM, self-efficacy and facilitating conditions. Keywords: agritourism tourists, SEM, TPB, tourist, visit decision